Not all data are equal: Influence of data type and amount in spatial conservation prioritisation. Issue 11 (16th October 2018) - Kujala, Heini; Lahoz‐Monfort, José Joaquín; Elith, Jane; Moilanen, Atte
Abstract: Decisions about land use significantly influence biodiversity globally. The field of spatial conservation prioritisation explores allocation of conservation effort, including for reserve network expansion, targeting habitat restoration, or minimising ecological impacts of development. Inevitably, the utility of such planning depends on the quantity and quality input data, including spatial information on biodiversity, threats, and cost of action. In this work we systematically develop understanding about the significance of these different data types in spatial conservation prioritisation. We clarify the common ways different data types enter an analysis, develop mathematical models to understand the effects of data in spatial prioritisation, and survey literature to establish typical quantities of different types of data used. We use Jackknife analysis to derive the expected change in site values, when a single new data layer is added to a prioritisation. We validate mathematical formulae for expected impacts using simulations. A survey of scientific literature reveals that typical spatial prioritisation analyses include hundreds of biodiversity feature layers (species, habitat types, ecosystem services), but the count of cost, threat or habitat condition layers is typically 0–5. Due to these differences, and the mathematical formulations commonly used to combine data types, the influence of a single cost, threat, or habitat condition data layer can be an order or two higher than the influence of a single biodiversity feature layer. In a classical cost‐effectiveness formulation (benefits divided by costs, B/C) the influence of a single cost layer can even be as large as the joint influence of thousands of species distributions. We also clarify how changes in data impact site values and spatial priority rankings differently, with the latter being further influenced by data correlations, the spread of numeric values inside data layers and other data characteristics. For example, costs influence priorities significantly if cost is positively correlated with biodiversity, but the correlation is the other way around for biodiversity and habitat condition. This work helps conservation practitioners to direct efforts when collating data for spatial conservation planning. It also helps decision makers understand where to focus attention when interpreting conservation plans and their uncertainties. Foreign Language AbstractAbstracto : Las decisiones sobre el uso de la tierra influyen significativamente en la biodiversidad a nivel mundial. El campo de la priorización espacial de la conservación explora la asignación del esfuerzo de conservación, incluida para la expansión de la red de reservas naturales, para focalizar la restauración de hábitat o la minimización de los impactos ecológicos del desarrollo. Inevitablemente, la utilidad de tal planificación depende de la cantidad y la calidad de los datos utilizados, incluida la información espacial sobre la distribución de biodiversidad, amenazas y coste de las intervenciones. En este trabajo, desarrollamos una exploración sistemática sobre la importancia de los diferentes tipos de datos en la priorización espacial de la conservación. Clarificamos las formas en las que los diferentes tipos de datos se utilizan comúnmente en el análisis, desarrollamos modelos matemáticos para comprender los efectos de los datos en la priorización espacial y revisamos la literatura para establecer las cantidades típicas de los diferentes tipos de datos utilizados. Usamos el análisis de Jackknife para derivar el cambio esperado en los valores del sitio, cuando se agrega una nueva capa de datos a una priorización espacial. Validamos las fórmulas matemáticas usando simulaciones. Una revisión de la literatura científica revela que los análisis típicos de priorización espacial incluyen cientos de capas de características de biodiversidad (especies, tipos de hábitats, servicios ecosistémicos), pero la cantidad de capas de coste, amenaza o condición de hábitat suele ser entre 0 y 5. Debido a estas diferencias, y las fórmulas matemáticas usadas comúnmente para combinar tipos de datos, la influencia de una única capa de coste, amenaza o condición del hábitat puede ser un orden o dos de magnitud más alta que la influencia de una sola capa de características de biodiversidad. En una formulación clásica de rentabilidad (beneficios divididos por costes, B/C), la influencia de una sola capa de costes puede ser tan grande como la influencia conjunta de miles de capas de distribución de especies. También aclaramos cómo los cambios en los datos impactan los valores del sitio y el ranking de prioridad espacial de forma diferente, siendo este último influenciado también por las correlaciones de datos, la dispersión de los valores numéricos dentro de las capas de datos y otras características de los datos. Por ejemplo, los costes influyen significativamente en las prioridades si el coste se correlaciona positivamente con la biodiversidad, pero la correlación es de signo inverso para la biodiversidad y la condición del hábitat. Este estudio ayuda a los profesionales de la conservación a focalizar los esfuerzos de recopilar datos para la planificación espacial de la conservación. También ayuda a los responsables de la toma de decisiones a comprender dónde centrar la atención cuando interpretan los planes de conservación y sus incertidumbres.